Blivande historielärares förståelse av mångfaldsfrågor i ett historiedidaktiskt perspektiv - Ylva Wibaeus (Educare)
Teaching history in a diverse and plural society: history teacher students´ understanding of class, gender and ethnicity from the perspective of history didactics